Christianity after religion: the end of church and the birth of a new spiritual awakening - Bass, Diana Butler (HarperOne, 2013)
The beginning -- The end of the beginning -- Questioning the old gods -- When religion fails -- Believing -- Behaving -- Belonging -- The great reversal -- Great awakening -- Performing awakening